Online Communication to Elderly Group - ไวยเจริญ, อริสรา (Siam Communication Review, 2017)
The purpose of this article is to study the means to communicate with the elderly, a fast-growing population with high purchasing power. This group of consumers share some behavioral traits. They spend 1-2 hours a day online, chatting and sending line stickers. On weekends, they enjoy shopping for a wide range of products including food supplements, cosmetic etc. To effectively reach this group of consumers through online communication, it is important to deliver the right message at the right time. In terms of content, the message should be direct, sincere, updated, and positive. Avoid such words and phrases as ‘the old’ or ‘the elderly’ because the audience may find it offensive as they consider themselves still fit and never too old to enjoy life. It is advisable to send messages with appreciation and create friendly relationship. At the same time, offline media should also be used to create greater awareness.